Pengaruh Utang dan Siklus Konversi Kas pada Kinerja Keuangan Perusahaan - Anggi Lestari; Henny Wirianata (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2025)
The purpose of this study is to obtain empirical evidence regarding the effect of short-term debt, long-term debt, total debt, and cash conversion cycle on financial performance in consumer cyclical and non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The purposive sampling method was used in this study with a total of 213 data from 71 companies for 3 years. The data analysis technique was carried out using multiple regression analysis, and data testing was carried out using the Eviews 12 application. The findings of this study indicate that short term debt has a significant negative effect on financial performance, long term debt has a significant negative effect on financial performance, total debt has a significant negative effect on financial performance, and cash conversion cycle has a significant negative effect on financial performance.